The Seduction of Avalon: The Pilgrimage to Goddess and the Affect of the Tour - Beard-Moose, Christina (Pomegranate, 2016)
Thousands of women, and men, have made the effort to go on pilgrimage due to epiphany or research or distrust of their née religions on a Pagan path. That path leads them to an ancient Celtic—or at least a simulacrum—way of being. They, we are drawn to the sites/sights and sounds of a European “homeland” we have never seen before. How do these people, many with non-European backgrounds, come to this particular pilgrimage? Why search for Avalon? This article looks at the phenomena that pulls a stranger/tourist/pilgrim population to a “homeland” they have never seen, never experienced, and only came to as an adult making a decision after searching, not as an enculturated child. Further, this article discusses those “quasi-Stendhalian” epiphanies that are evoked when one reaches such “sacred ground.” Women who come in pilgrimage to find the Goddess – in whatever form they might think of her – have a multitude of experiences at various venues and “hotspots” that abound in Glastonbury. Whether it is going to sacred water, either Chalice Well or the White Spring, climbing the Tor to the summit or as far as one can get, or attending one of the Goddess-centered events throughout the year, pilgrims come to connect with She That Is and with each other. What is this visceral experience of anticipation and completion upon reaching the goal at Glastonbury/Avalon? This is an introductory article to search for these answers.